PENGEMBANGAN DASHBOARD ANALITIK PADA APLIKASI TRACER STUDI UNTUK MANAJEMEN DATA ALUMNI DI UNIVERSITAS UDAYANA - Ida Bagus Wahyu Semara Kamajaya; Luh Arida Ayu Rahning Putri Putri; Made Agung Raharja (Jurnal Pengabdian Informatika, 2026)
Alumni data management plays a crucial role in graduate evaluation and the development of higher education institutions. This development aims to create an analytical dashboard within the tracer study application at Udayana University to facilitate interactive and real-time alumni data management. The implementation method includes feature design, technical development, system testing, socialization to tracer study administrators, and evaluation and refinement based on user feedback. The results show that the dashboard is capable of presenting alumni questionnaire data in easy-to-understand charts and tables, simplifying career pattern identification, supporting centralized data management, and enabling strategic decision-making. The socialization phase provided valuable feedback for feature improvements, while the main challenges—such as integrating heterogeneous data and designing a user-friendly interface—remain key focuses for future development. This dashboard is expected to enhance alumni data management efficiency and strengthen the university's network with the industry.